The law of public contracts in Spain: news and proposals for the future - Gimeno Feliu, José María (2021)
This paper gives an account of the regulation of public procurement in Spain with prospective ideas on what the future should be. Attention is paid to the main lines of Spanish regulation, and its aims, to end with some propositional conclusions on the regulatory rationale.